2021
DOI: 10.11591/ijere.v10i1.20972
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sorogan method in learning history to increase historical understanding and historical awareness

Abstract: <span>The purpose of this study was to examine the influence of the <em>sorogan </em>method in history learning to improve students' historical understanding and historical awareness. The research method used a quasi-experimental nonequivalent control group design, and the sampling technique used a cluster sampling with a sample size of 96 students. Collecting data through observation, interviews, and tests of historical understanding and awareness. Meanwhile, data analysis to determine the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
0
13
0
3
Order By: Relevance
“…However, the fact is reversed, a negative paradigm always haunts history learning which is difficult to remove, so that in its implementation and meaning it is still often misunderstood by most students. The problem is certainly inseparable from learning which tends to be conventional so that students are less interested and bring up pragmatic practical thinking habits [43], [44]. So, it is very necessary to learn history in today's digital era, teacher professionalism is needed in designing and designing history learning by utilizing technological sophistication or digital, which can make it easier to introduce historical concepts to students [45].…”
Section: Discussionmentioning
confidence: 99%
“…However, the fact is reversed, a negative paradigm always haunts history learning which is difficult to remove, so that in its implementation and meaning it is still often misunderstood by most students. The problem is certainly inseparable from learning which tends to be conventional so that students are less interested and bring up pragmatic practical thinking habits [43], [44]. So, it is very necessary to learn history in today's digital era, teacher professionalism is needed in designing and designing history learning by utilizing technological sophistication or digital, which can make it easier to introduce historical concepts to students [45].…”
Section: Discussionmentioning
confidence: 99%
“…It means if students' historical awareness is high, the students' nationalistic attitudes will be also high. Fadli et al found that there is a relationship between historical awareness and nationalism, meaning that historical awareness in students will affect their nationalism attitude [36]. The attitude of nationalism cannot be grown without historical awareness, so that historical awareness has a significant and positive relationship to the attitude of nationalism [37].…”
Section: The Correlation Multicultural Historical Awareness To Nation...mentioning
confidence: 99%
“…Thus, it can be concluded that the independent variable, namely the history module, simultaneously However, the myriad uses of history become real if the awareness to think critically and act rationally begins to be built (Fadli, et al, 2021). This mindset and action can be obtained by developing historical awareness, moreover the recent phenomenon (or criminal case) 'using' history as its main ammunition (Amboro, 2015).…”
Section: Simple Regression Analysismentioning
confidence: 99%